Strengthening care in collaboration with people with lived experience of psychosis in Uganda (SCAPE-U): A protocol for a cluster randomized controlled feasibility trial - Byamah Brian Mutamba; Sauharda Rai; Lynn Semakula; David Cappo; Laura Asher; Wilfred Gwaikolo; Brandon A. Kohrt (Pilot and Feasibility Studies)
Abstract Background Mental health services are most effective and equitable when designed, delivered, and evaluated in collaboration with People With Lived Experience of mental health conditions (PWLE). However, PWLE are rarely involved in health systems strengthening, and when they are, it is limited to specific components (e.g., peer helpers) rather than multi-tiered collaboration in the full continuum of home to community to facility based services. Moreover, programs that do involve PWLE typically involve people with a history of substance use conditions or common mental disorders. The collaboration of People With Lived Experience of Psychosis (PWLP) is especially rare. Therefore, we aim to explore the feasibility of collaborating with PWLP for health systems strengthening in this feasibility trial. Methods This pilot cluster randomized controlled feasibility trial will randomize 36 health facilities to a standard implementation arm where primary care workers (PCW) will be trained by mental health specialists (control), or a collaborative care model with added co-facilitation of PCW trainings by PWLP as well as home visits by PWLP to service users (intervention). The intervention condition is referred to as “Strengthening CAre in collaboration with People with lived Experience of psychosis in Uganda” (SCAPE-U). The 36 health facilities will be distributed across six clusters with three clusters in each arm. PhotoVoice will be used to train PWLP to be co-facilitators of PCW training and provide home-based support to service users in the intervention arm. The primary outcomes of the feasibility trial will be the feasibility, acceptability, and safety of collaborating with PWLP. Data will also be collected on individual-level outcomes for PCWs, and service users to inform the feasibility of data collection and obtain effect size estimates. Discussion Findings from this feasibility trial will inform a fully powered trial to evaluate the benefits of an implementation strategy characterized by collaboration with PWLP across the continuum of healthcare services. Trial registration ClinicalTrials.gov. number: NCT05863572. Date of registration: May 18, 2023. URL of trial registry record: https://clinicaltrials.gov/study/NCT05863572?term=NCT05863572&rank=1 .